The development of IBS structure panel using revit software - Supar, Khairi; Hisyamudin, Nur Atiqah Izzati; Muhamad Amin Abdulla, Muhammad Nurarif Amsyar; Mohd Noor, Nurul Fatin Shazwani; Idris, Nur'Ain; Ahmad, Hilton (2024)
Autodesk's Revit is a sophisticated Building Information Modelling (BIM) software that transforms the way architects, engineers, and construction professionals create, collaborate, and visualize their projects. Revit has become the industry standard for producing and maintaining complex building models due to its rich set of tools and capabilities. Revit, at its heart, allows users to generate sophisticated 3D models that span the whole building's lifespan. These models function as a digital representation of the actual structure and include precise information about its components, materials, and systems. Building Information Modelling (BIM) software is made by Autodesk and is called Revit. By using Revit, it can create a conventional column family, IBS column family, conventional beam family, and IBS beam family. This project also showed extrusion for conventional column family, IBS column family, conventional beam family, and IBS beam family. Revit's parametric modeling capabilities are a game changer in the field of architecture. Families, as parametric objects, allow dynamic modifications and real-time updates throughout the project. By establishing relationships between different family parameters, such as dimensions, materials, and geometry, designers can easily adjust the model and see the effect reflected across the entire project. This parametric flexibility reduces errors, streamlines design iterations, and ultimately leads to more efficient and accurate construction documentation. The result of this project highlighted conventional column model design, IBS column model design, conventional beam model design, and IBS beam model design. The objective of this project is to create a library of IBS panels that are commonly used in construction and compare the advantages between IBS panels and conventional panels for the component structure